$\lim _{x \rightarrow \frac{\pi}{6}} \frac{\cot ^{2} x-3}{\operatorname{cosec} x-2}$


$\lim _{x \rightarrow \frac{\pi}{6}} \frac{\cot ^{2} x-3}{\operatorname{cosec} x-2}$


Given $\lim _{x \rightarrow \frac{\pi}{6}} \frac{\cot ^{2} x-3}{\operatorname{cosec} x-2}$

We know that

$\cot ^{2} x=\operatorname{cosec}^{2} x-1$

By using this in given equation we get

$\Rightarrow$ $\lim _{x \rightarrow \frac{\pi}{4}} \frac{\left(\operatorname{cosec}^{2} x-1\right)-3}{\operatorname{cosec} x-2}=\lim _{x \rightarrow \frac{\pi}{4}} \frac{\operatorname{cosec}^{2} x-4}{\operatorname{cosec} x-2}$

Again using $a^{2}-b^{2}$ identity the above equation can be written as

$\Rightarrow$$\lim _{x \rightarrow \frac{\pi}{6}} \frac{\operatorname{cosec}^{2} x-4}{\operatorname{cosec} x-2}=\lim _{x \rightarrow \frac{\pi}{6}} \frac{(\operatorname{cosec} x-2)(\operatorname{cosec} x+2)}{\operatorname{cosec} x-2}$

On simplification and applying the limits we get

$\Rightarrow$$\lim _{x \rightarrow \frac{\pi}{6}} \frac{(\operatorname{cosec} x-2)(\operatorname{cosecx}+2)}{\operatorname{cosec} x-2}=\lim _{x \rightarrow \frac{\pi}{6}}(\operatorname{cosecx}+2)=2+2=4$

$\Rightarrow$$\lim _{x \rightarrow \frac{-1}{6}} \frac{\cot ^{2} x-3}{\operatorname{cosec} x-2}=4$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now